KEUANGAN SEDERHANA DAN PENYAJIAN LAPORAN KEUANGAN MENGGUNAKAN SOFTWARE AKUNTANSI BERBASIS EXCEL PADA CLOTHING “DOBUJACK” KOTA BANDUNG - Dodi Supriyanto; Rukanda Ahmad Sulanjana; Iwan Mulyana (STIE Ekuitas, 2020)
Dobujack is a privately owned company engaged in the manufacturing industry of clothing, bags, shoes, etc. In running its business, Dobujack already has workshops and showrooms to produce and market the products it produces. Dobujack has a production capacity of 10,000 pieces of T Shirts per month in all sizes, 200 jackets with all size sizes (L, M, XL, and S) and 5,000 pairs of shoes with a size that is held by 25 (twenty five) employees on 2 ( two) workshops covering 1,300 m2, and the remainder are produced with the maklun system. The purpose of this study is to find out about the process of applying financial management in terms of presenting financial statements of individual industrial companies named Dobujack. This research uses descriptive verification method, which is to find out the description of the object under study in accordance with real conditions in the field. In terms of data collection, the compiler does it by using interview techniques, literature review and on the spot directly to the object under study. Based on the results of the study showed that the activities of this company have not fully used the application of good financial management, the financial statements used are limited to knowing cash and sales positions. And online transaction reports can be accessed only by the owner. With this dedication research, it is hoped that this clothing company will be able to present financial reports properly and correctly according to accounting standards. This is done in order to anticipate the company's progress in the future.